COMMON GRAMMATICAL MISTAKE FOR ENGLISH’S STUDENTS OFTADRIS ENGLISH LANGUAGE - Nur Azizah (International Journal of Teaching and Learning, 2026)
This paper is aimed to investigate the common grammatical mistake and describe the findings descriptively as possible. This research used descriptive qualitative as a research design. The instruments used were observation and interview. The interview is used unstructured interview to get free question and answer about the topic. Interview and observation did in two classes of third and five semesters by joining the activities in the classroom. Most of the students in the classroom are eight students in third semesters and eight students in five semesters. The total number of the students are 18 students. Ten students are female and six students are male. The data was gained from the lecture of writing. In analyzing the data, the researcher used snowballing technique. It means the first data became alternative finding until the researcher found the final findings. The final finding is drawn descriptively. The finding of this research is only three students good grammar from 18 students. It was concluded that the English students in third and five semesnter of Tadris English language still get common mistake in grammar.